Real-world antithrombotic strategies in patients with atrial fibrillation and recently developed acute coronary syndrome - Hiroshi Iwata; Katsumi Miyauchi; Shuko Nojiri; Yuji Nishizaki; Yuichi Chikata; Hiroyuki Daida; Akashi Akasaka; Yukio Ozaki; Yoshihisa Nakagawa; Kenichi Tsujita; Takafumi Ueno; Ken Kozuma; et al. (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: The antithrombotic strategy for patients with atrial fibrillation (AF) and coronary artery disease following percutaneous coronary intervention is shifting towards less intensive. Nevertheless, for patients with AF and acute coronary syndrome (ACS), an optimal antithrombotic strategy is yet to be established. Methods and results: We conducted a multi-center cohort study involving 146 Japanese centers that had prospectively registered 460 patients with AF and ACS followed for 2 years. Primary endpoint was the composite of thrombotic and bleeding events, and secondary endpoints included heart failure hospitalization. At the time of study registration, 86 % of participants had received direct oral anticoagulants (DOACs) and 75 % had received aspirin-based triple antithrombotic therapy (TAT) between March 2017 and August 2019. Apixaban was the most frequently used DOAC (29 %). While the proportion of anticoagulants did not change according to the time course, the intensity of antiplatelets significantly attenuated over time (dual antiplatelet at baseline: 75 %, and at 2-years: 7 %). The cumulative incidence of the primary outcome measure was similar in patients with warfarin and DOACs. However, the risk of heart failure hospitalization was significantly higher in those with warfarin compared to DOACs (Hazard ratio: 2.8, 95 % confidence interval: 1.1–5.8, p = 0.022). Conclusions: The present findings suggest the appropriate optimization of antithrombotic medication balancing in patients with AF and ACS in Japan by reducing the intensity of antiplatelets during the study period.